Efektivitas Penerapan Sistem Aplikasi INLISLITE (Integrated Library System) Pada Kegiatan Penginputan Data Dinas Perpustakaan Dan Kearsipan Kabupaten Aceh Barat - Alfi Rahmi; Najamudin Najamudin (Journal of Social Politics and Governance (JSPG), 2022)
The purpose of this study was to find out whether the INLISLITE application was effective or not in the system at the West Aceh District Library and Archives Agency. This study uses the theory of effectiveness prosed by Madiasmo. Data collection techniques in this study were carried out by means of observation, interview, and documention. The result of this research show that the application of the INLISLITE application system at the Library and Archives Service of West Aceh Regency has been effectively implemented. The obstacles faced by librarians in noerating the INLISLITE application and the lack of human resources who are expert in Information Techonoly (IT) knowledge as well as several constraints on the selver. The benefits or opportunities obtanited in using the INLISLITE application are very time efficient in inputting colection that appear in the OPAC and on the bookshelf.